Signaling pathways in macrophages: molecular mechanisms and therapeutic targets - Ming Li; Mengjie Wang; Yuanjia Wen; Hongfei Zhang; Guang‐Nian Zhao; Qinglei Gao (MedComm, 2023)
Abstract Macrophages play diverse roles in development, homeostasis, and immunity. Accordingly, the dysfunction of macrophages is involved in the occurrence and progression of various diseases, such as coronavirus disease 2019 and atherosclerosis. The protective or pathogenic effect that macrophages exert in different conditions largely depends on their functional plasticity, which is regulated via signal transduction such as Janus kinase–signal transducer and activator of transcription, Wnt and Notch pathways, stimulated by environmental cues. Over the past few decades, the molecular mechanisms of signaling pathways in macrophages have been gradually elucidated, providing more alternative therapeutic targets for diseases treatment. Here, we provide an overview of the basic physiology of macrophages and expound the regulatory pathways within them. We also address the crucial role macrophages play in the pathogenesis of diseases, including autoimmune, neurodegenerative, metabolic, infectious diseases, and cancer, with a focus on advances in macrophage‐targeted strategies exploring modulation of components and regulators of signaling pathways. Last, we discuss the challenges and possible solutions of macrophage‐targeted therapy in clinical applications. We hope that this comprehensive review will provide directions for further research on therapeutic strategies targeting macrophage signaling pathways, which are promising to improve the efficacy of disease treatment.